THE DEVELOPMENT OF CLASSROOM POLICIES THROUGH DISCUSSION BETWEEN TEACHERS AND STUDENTS - Nugroho, Kurniawan Yudhi (Jurnal Pendidikan Bahasa dan Sastra, 2016)
AbstractÂ This article presented the result in the interview and discussion between teacher and students aimed at revealing studentsâ€™ perception on the previous course program. Of the interview and discussion, it was observed that the previous program was not conducted optimally in term of knowledge and oral language proficiency development where the students perceived it was very important. In order to bridge the gap, discussion was arranged. As a result, mutual agreement between the teacher and the students was achieved. In order to materialize the goal of learning both the teacher and the students agreed upon: 1) using English as a medium of communication during the learning program, 2) learning activities were conducted through presentation and discussion, 3) it was highly expected that students came to the class on time, tolerance for late comers would only be 10 minutes, 4) it was highly required that students met 75% of attendance at minimum, in order to participate in the final exam, 5) Assignment must be submitted punctually based on the schedule, 6) students were endorsed to actively participate in the learning activities.Keywords: classroom policies, discussion, speaking proficiency, knowledge development